Pemahaman Mahasiswa Perbankan Syariah Terhadap Job Career di Lembaga Keuangan Syariah Non Bank - kurniawati meylianingrum (Jurnal Ilmiah Ekonomi Islam, 2020)
This study aims to determine the integration of understanding between theories that have been studied by students of Islamic banking study programs with practices that occur in the workforce, and also prepare mature human resources to face the development of non-bank Islamic financial institutions in Indonesia. The method used is a qualitative analysis with an interpretive approach. With the interpretive approach the writer tries to understand every explanation from the sources as well as ongoing education, experience, and developmental changes that occur. The results of this study are that students understand well the job careers in non-bank Islamic financial institutions such as Takaful family Islamic insurance institutions, amil zakat institutions, and Baitul Maal wa Tamwil. Unlike the Islamic banking financial institutions, working in non-bank Islamic financial institutions such as Islamic insurance, amil zakat institutions, and Baitul Maal wa Tamwil prioritize the social value of the community. Relationships with customers are not just customers with institutions, but also the creation of family relationships among people. Factors that strengthen student understanding of job careers in non-bank Islamic financial institutions